Efeitos iniciais da ovariectomia e do tratamento com estrógeno e isoflavonas da soja, isolados e associados, na reparação óssea alveolar e no útero de ratas - Silveira, Vanessa Ávila Sarmento [UNESP] (2007)
Due to the adverse effects of estrogen, new therapies have been proposed, such as soy isoflavones. However, their effects on bone repair and uterus epithelium remain unclear. The aim of this work was to study the acute effects of ovariectomy and treatment with estrogen and soy isoflavones, isolated or in association, on rat bone repair and uterus epithelium. 120 rats were used; 96 ovariectomized and 24 Sham-operated (SHAM). The ovariectomized rats were dibided into 4 groups, receiving orally: 1 mg/kg/day of 17 'beta'-estradiol valerate(OVZ-E); 15mg/kg/day of isoflavones (OVZ-I); associated treatments (OVZ-A); and vehile (OVZ). SHAM rats received vehicle. Treatment began on the ovariectomy day. The lower first molar was removed on both sides 15 days after ovariectomy. The rats received the treatment until sacrificed, which occurred at seven, 21 and 45 days after dental extraction. The uterus was submitted to histological analyses and the mandible to histological, histomorphometric, backscattered electron microscopy (BSE) and immunohistochemistry analyses. Concerning bone repair, no difference was observed in trabecular volume between the OVZ and SHAM groups for each period. Histological analysis and BSE revealed changes in bone microarchitecture after 45 days. Verification showed that the SHAM group presented a higher mean osteoid volume at seven days compared to the OVZ and OVZ-E groups and that the OVZ-A group showed the highest mean for this period. The number of mast cells tended to be higher in the OVZ group at 45 days. Strong expression of TGF-'beta' was observed at seven days, which diminished over time. The OVZ-E group presented the lowest mineral apposition rate at seven days. No difference was observed for the remaining periods. The SHAM, OVZ-E and OVZ-A...